Bioorthogonal metabolic glycoengineering of human larynx carcinoma (HEp-2) cells targeting sialic acid - Homann, Arne; Qamar, Riaz-ul; Serim, Sevnur; Dersch, Petra; Seibel, Jürgen (Beilstein Journal of Organic Chemistry, 2010)
Sialic acids are located at the termini of mammalian cell-surface glycostructures, which participate in essential interaction processes including adhesion of pathogens prior to infection and immunogenicity. Here we present the synthesis and bioorthogonal metabolic incorporation of the sialic acid analogue N-(1-oxohex-5-ynyl)neuraminic acid (Neu5Hex) into the cell-surface glycocalyx of a human larynx carcinoma cell line (HEp-2) and its fluorescence labelling by click chemistry.
Keywords: bioorthogonal metabolic glycoengineering; click chemistry; sialic acid